Understanding the element segregation and phase separation in the Ce-substituted Nd-(Fe,Co)-B based alloys - L. Z. Zhao (Nature Portfolio, 2018)
Abstract Ce substituted Nd2Fe14B (2:14:1)-type permanent magnets have shown increasing potential in the applications due to their high properties/cost ratio. However, the element segregation and phase separation in the Ce substituted magnets have not been fully understood yet. In this work, (Nd1−xCex)25Fe40Co20Al4B11 alloys with high coercivities were prepared by copper mold casting. Based on detailed microstructure and composition analysis, the segregation of rare earth (RE) elements was observed in the as-cast alloys. Nd element prefers to enter into the 2:14:1 phase and the Ce element enter into the 1:2 phase. The existence of the 1:2 phase can promote the element segregation. The alloy shows an abnormal increase of coercivity from 641 kA/m for x = 0.2 to 863 kA/m for x = 0.3. This increase could be attributed to the phase separation of the 2:14:1 phase, which has been confirmed by the microstructural characterization. The present data provides useful information for exploring Ce-containing Nd-Fe-B magnets.